Combination of Kansei Engineering and Ergonomic Function Deployment (EFD) in Designing Ergonomic Products: A Review Study - Niken Kristin Silitonga; Anizar; Rosnani Ginting (Jurnal Sistem Teknik Industri, 2026)
Industrial competition encourages product development to focus not only on functionality but also on user satisfaction, comfort, and safety. The integration of Kansei Engineering (KE) and Ergonomic Function Deployment (EFD) has attracted significant attention in ergonomic product design research, as it enables the systematic translation of users’ emotional needs into technical specifications. This article presents a literature review study that examines the application and integration of KE and EFD methods in ergonomic product design. The review is based on an analysis of national and international scientific journals addressing ergonomics, Kansei Engineering, and Ergonomic Function Deployment. The results indicate that the integration of KE and EFD effectively improves user comfort, safety, and satisfaction, while reducing the risk of musculoskeletal disorders and enhancing work productivity. Successful implementation is influenced by accurate identification of user requirements, the use of anthropometric data, ergonomic assessment tools, and close collaboration between designers and users. Furthermore, several studies highlight the importance of sustainable design by considering efficiency, occupational health, and product competitiveness. Overall, this review provides a comprehensive understanding of the potential and benefits of integrating Kansei Engineering and Ergonomic Function Deployment in ergonomic product design and offers a foundation for further research and practical implementation across various industrial sectors.